Awareness status of sightseeing bus entrepreneurs: A case study in rural areas of Thailand - S. Jomnonkwao; S. Siridhara; V. Ratanavaraha (Lowland Technology International, 2015)
The main objective of this study is to contemplate the awareness of entrepreneurs of sightseeing bus services as used by Thai travelers for private group tours and field trips through four considerations including 1) provision of convenient and safe buses; 2) provision of customer service satisfaction; 3) provision of experienced and well-behaved bus drivers; and 4) provision of bus services under travel safety. The study was carried out through interviews with 25 bus company representatives and found that factors which were raised the highest priority by entrepreneurs are provision of bus drivers having a valid driving license matching the vehicle type according to law and the provision of regular bus cleaning service. While a factor related to the provision of auto massage seats for relaxation was overlooked by all respondents. Moreover, the research team classified factors into 5 groups from A to E (highest to lowest awareness) using clustering analysis possibly making it easier to develop policy interventions appropriate with awareness of each entrepreneur group